(untitled) (Asian Journal of Agriculture, 2025)
Abstract. Rozaki Z, Al Hadi SS, Rahmawati N, Triyono, Ardila RA, Pamungkas HW, Fathurrohman YE. 2025. The feasibility insights of organic rice farming from Central Java and Yogyakarta, Indonesia. Asian J Agric 9: 122-130. Agricultural practices are increasingly moving towards environmentally friendly and health-conscious approaches, including organic rice farming. This is also supported by the increasing demand for organic rice among consumers who care about health and the environment. Therefore, this study aimed to evaluate the feasibility of organic rice farming in Yogyakarta and Central Java considering costs, income, profitability, and sustainability among 150 organic rice farmers randomly selected from five districts. The results showed that the average cost incurred for organic rice farming was IDR 11,832,023 per hectare per year, while the income generated reached IDR 14,943,216 per hectare per year. Based on the data, the net income of farmers was IDR 3,111,193 per hectare per year. The feasibility analysis using the R/C ratio showed a value of IDR 1.26, indicating that for every IDR 1.00 spent, farmers earn IDR 1.26, with a profit of IDR 0.26. This implies that organic rice farming is not only environmentally friendly but also financially feasible, with favorable cost-benefit ratios, as it reduces the costs incurred by farmers. In conclusion, the development of organic rice farming has great potential, specifically since consumers, through their demand for organic rice, play a crucial and influential role in its growth.